Modelling and PID control of antilock braking system with wheel slip reduction to improve braking performance. (1st January 2013) - Aparow, Vimal Rau; Ahmad, Fauzi; Hudha, Khisbullah; Jamaluddin, Hishamuddin
This paper presents the development of a PID controller for an Antilock Braking System (ABS) using vehicle longitudinal model. A Five Degree of Freedom (5-DOF) vehicle longitudinal dynamic model was derived and integrated with an analytical tyre dynamics, the Magic Tyre model. Several transient handling tests are performed such as sudden acceleration and sudden braking test to validate the vehicle model. The model is used as a plant to develop an antilock braking system to control longitudinal slip and reduce the stopping distance. A hydraulic brake model was developed as the brake actuator to produce brake torque. A conventional PID controller has been implemented to deal with the strong nonlinearity in the design of ABS controller. The proposed ABS control structure is shown able to significantly reduce stopping distance and control the longitudinal slip during heavy braking.